Locational Marginal Pricing: A Fundamental Reconsideration - Leigh Tesfatsion (IEEE Open Access Journal of Power and Energy)
This study establishes that Locational Marginal Pricing (LMP) is conceptually problematic for grid-supported centrally-managed wholesale power markets transitioning to decarbonized grid operations with increasingly diverse participants, hence with increasingly uncertain and volatile net loads. LMP assigns a common per-unit price LMP(b,T) ( ${\$}$ /MWh) to each next unit (MWh) of grid-delivered energy, conditional on delivery location b and delivery period T. However, this entails a serious many-to-one benefit/cost measurement error: namely, the valuation of this next unit by a market participant or system operator will typically depend strongly on the dynamic attributes of the path of power injections and/or withdrawals (MW) used to implement its delivery at b during T. One option is to muddle through, forcing market participants and system operators to express benefit/cost valuations for next units of grid-delivered energy in per-unit form without regard for the true benefits and costs of flexible power delivery. Another option, advocated in this study, is to explore conceptually-coherent nodal multi-interval pricing mechanisms permitting grids to function efficiently as flexibility-support insurance mechanisms, i.e., as mechanisms enabling just-in-time nodal power deliveries to meet just-in-time nodal power demands as well as system reliability requirements.